Lean production as efficiency improvement tool in boat building process / Rasyidah Othman - Othman, Rasyidah (2009)
The improvement in boatbuilding or shipbuilding process has become a focus and has received huge attention from the Malaysian boat builders and shipbuilders. Furthermore, shipbuilders around the world are moving and looking forward to optimizing their resources in order to become a world-class shipbuilder so as to compete with Asian shipbuilders particularly from South Korea, China and Japan. For any shipyards that have lack of resources, knowledge in preparing effective planning strategies and having ineffective methods of production, the possible outcome is to invite displeasure amongst clients for not being able to deliver the quality product on time. In this research, the application of lean principles and tools in identifying the production planning problems at Kay Marine Sdn. Bhd. (KMSB) has been explored, right from the problems identification to improvement strategy of the boatbuilding process. Lean tools used in this research are: Cause and Effect Diagram, Five Whys, Work Study Method, Group Technology and Assembly Line Balancing with Takt Time. Comparison between proposed methods against the current method was done to identify the improvements in terms of throughput, work- in-progress (WIP) inventory occupancy, labour productivity, efficiency, labour cost and penalty. Most of these metrics can be improved by at least 40%. With all of these improvements, it can be deduced that KMSB can be more competitive in boatbuilding production; while at the same time enjoys the workers' improved competency and confidence.